Methane emissions from California dairies estimated using novel climate metric Global Warming Potential Star show improved agreement with modeled warming dynamics - Pressman, Eleanor M.; Liu, Shule; Mitloehner, Frank M. (Frontiers in Sustainable Food Systems, 2023)
Introduction Carbon dioxide (CO2) and methane (CH4) are two of the primary greenhouse gases (GHG) responsible for global warming. The “stock gas” CO2 accumulates in the atmosphere even if rates of CO2 emission decline. In contrast, the “flow gas” CH4 has an e-folding time of about 12 years and is removed from the atmosphere in a relatively short period of time. The climate impacts of cumulative pollutants such as CO2 and short-lived climate pollutants (SLCP) such as CH4 are often compared using Global Warming Potential (GWP), a metric that converts non-CO2 GHG into CO2-equivalent emissions. However, GWP has been criticized for overestimating the heating effects of declining SLCP emissions and conversely underestimating the heating impact of increasing SLCP emissions. Accurate quantification of the temperature effects of different CH4 emissions scenarios is particularly important to fully understanding the climate impacts of animal agriculture, whose GHG emissions are dominated by CH4. Methods A modified GWP metric known as Global Warming Potential Star (GWP*) has been developed to directly quantify the relationship between SLCP emissions and temperature change, which GWP cannot do. In this California dairy sector case study, we contrasted GWP- versus GWP*-based estimates of historical warming dynamics of enteric and manure CH4 from lactating dairy cattle. We predicted future dairy CH4 emissions under business-as-usual and reduction scenarios and modeled the warming effects of these various emission scenarios. Results We found that average CO2 warming equivalent emissions given by GWP* were greater than those given by GWP under increasing annual CH4 emissions rates, but were lower under decreasing CH4 emissions rates. We also found that cumulative CO2 warming equivalent emissions given by GWP* matched modeled warming driven by decreasing CH4 emissions more accurately than those given by GWP. Discussion These results suggest that GWP* may provide a more accurate tool for quantifying SLCP emissions in temperature goal and emissions reduction-specific policy contexts.